Hudhud hi Aliguyon An Ifugao Harvest Song. [anthology].
In the mountainous regions of Northern Luzon, a hudhud is a long tale sung during special occasions. This particular long tale is sung during harvest. A favorite topic of the hudhud is a folk hero named Aliguyon, a brave warrior.
Found in: Philippine Folk Literature : The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.